"Otro" teatro español : supresión e inscripción en la escena española de los siglos XX y XXI - Delgado, Maria M. (Iberoamericana ; Vervuert, 2017)
'Other' Spanish Theatres challenges established opinions on modern Iberian theatre through a consideration of the roles of contrasting figures and companies who have impacted upon both the practice and the perception of Spanish and European stages. In this broad and detailed study, Delgado selects six subjects which map out alternative readings of a nation's theatrical innovation through the last century. These six subjects include Margarita Xirgu, Enrique Rambal, Mara̕ Casarest and Nuria Espert.